rstB Regulates Expression of the Photobacterium damselae subsp. damselae Major Virulence Factors Damselysin, Phobalysin P and Phobalysin C - Terceti, Mateus S.; Rivas, Amable J.; Alvarez, Laura; Noia, Manuel; Cava, Felipe; Osorio, Carlos R. (Frontiers in Microbiology, 2017)
The marine pathogenic bacterium Photobacterium damselae subsp. damselae causes septicemia in marine animals and in humans. The pPHDD1 plasmid-encoded hemolysins damselysin (Dly) and phobalysin P (PhlyP), and the chromosome-encoded hemolysin phobalysin C (PhlyC) constitute its main virulence factors. However, the mechanisms by which expression of these three hemolysins is regulated remain unknown. Here we report the isolation of a mini-Tn10 transposon mutant which showed a strong impairment in its hemolytic activity. The transposon disrupted a putative sensor histidine kinase gene vda_000600 (rstB), which together with vda_000601 (rstA) is predicted to encode a putative two-component regulatory system. This system showed to be homologous to the Vibrio cholerae CarSR/VprAB and Escherichia coli RstAB systems. Reconstruction of the mutant by allelic exchange of rstB showed equal impairment in hemolysis, and complementation with a plasmid expressing rstAB restored hemolysis to wild-type levels. Remarkably, we demonstrated by promoter expression analyses that the reduced hemolysis in the rstB mutant was accompanied by a strong decrease in transcription activities of the three hemolysin genes dly (damselysin), hlyApl (phobalysin P) and hlyAch (phobalysin C). Thus, RstB, encoded in the small chromosome, regulates plasmid and chromosomal virulence genes. We also found that reduced expression of the three virulence genes correlated with a strong decrease in virulence in a sea bass model, demonstrating that RstB constitutes a master regulator of the three P. damselae subsp. damselae hemolysins and plays critical roles in the pathogenicity of this bacterium. This study represents the first evidence of a direct role of a RstAB-like system in the regulation of bacterial toxins.